2016
DOI: 10.1111/nyas.13031
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B1 (thiamine) and dementia

Abstract: The earliest and perhaps best example of an interaction between nutrition and dementia is related to thiamine (vitamin B1). Throughout the last century, research showed that thiamine deficiency is associated with neurological problems, including cognitive deficits and encephalopathy. Multiple similarities exist between classical thiamine deficiency and Alzheimer’s disease (AD) in that both are associated with cognitive deficits and reductions in brain glucose metabolism. Thiamine-dependent enzymes are critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(123 citation statements)
references
References 54 publications
1
116
0
1
Order By: Relevance
“…Decreased TDP levels and thiamine-dependent enzymes activities were found in AD patients but not in patients with vascular dementia, frontotemporal dementia and Parkinson’s disease[9,16]. Our previous study demonstrated that thiamine metabolism can serve as a promising biomarker for AD diagnosis with high sensitivity and specificity over 80%[8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased TDP levels and thiamine-dependent enzymes activities were found in AD patients but not in patients with vascular dementia, frontotemporal dementia and Parkinson’s disease[9,16]. Our previous study demonstrated that thiamine metabolism can serve as a promising biomarker for AD diagnosis with high sensitivity and specificity over 80%[8].…”
Section: Discussionmentioning
confidence: 99%
“…Both TDP level[8,9,10,11] and activities of TDP-dependent enzymes[12,13,14,15] have been demonstrated to be significantly decreased in AD. Previous studies have demonstrated that thiamine deficiency can induce or aggravate AD-like pathologies, such as neuritic plaques, and hyperphosphorylation of tau, finally memory deficits[16]. Furthermore, benfotiamine supplementary, a lipid-soluble thiamine derivative, diminished AD-like pathologies and cognitive function in AD animal models[17].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Since hTK substrates and products are intermediates of other fundamental metabolic processes, such as glycolysis and the glucuronic acid pathway, [3] its activity is strictly related to treatment and prevention of various diseases. [8,9] In the case of brain dysfunctions [10] and diabetes mellitus, [11,12] regular hTK's activity has been monitored and related to prevention of these diseases. [4,5] Additionally, tumor cells growth has been blocked by inhibiting non-oxidative phase of PPP in which hTK is involved [6,7] and, moreover, the reduced activities of hTK have been linked to diseases affecting brain tissues, such as Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms observed in WKS include oculomotor disturbance, ataxia and confusion (acute symptoms), and amnesia and confabulation (chronic symptoms) [9] [10]. Rodent models of TD have been developed to examine the pathogenesis of these disorders [11].…”
mentioning
confidence: 99%